An Exploration of the Effect of Advertising Placement and Messaging on Urban Durban Zulu Professional Millennials’ Purchasing Decisions of Funeral Services. - Hlophe, Gugulethu (The IIE, 2022)
Presently, there is limited literature within the faculty of marketing regarding effective advertising messaging and media placement for funeral services (Coetzee, 2013). The marketing of unsought services, specifically funeral services, poses intrinsic unique challenges for marketers (Coetzee, 2013). This challenge provokes primary research question: Which advertising channels and messaging optimally influences urban Zulu Durban professional millennials’ purchasing decisions of funeral services? The funeral industry is growing in its competitiveness, thus needing to advertise to differentiate and grow (Hernández, 2013). Strategic advertising messaging and media buying is required to market such necessary yet unsought services (AMASA, 2018), in a manner that overcomes advertising avoidance (Kaçınma, Kaçınma, Kaçınma, Kaçınma & Varlığı, 2015). Millennials are a lucrative market (Maluleke, 2018)., thus vital for the growth of the funeral services businesses and industry as a whole. Through the interpretivist lens, qualitative data was obtained using semi-structured interviews to obtain detailed perceptual and behavioural data (Maree, 2019). 10 participants were obtained through non-probability convenience sampling. Findings indicated that price, word-of-mouth and brand experience are key determinants in funeral services purchasing decisions. Additionally, a diverse media mix, and creative informative content is required to connect with the target demographic. Further research is recommended to provide deeper insights that can be generalized to larger groups.
Keywords: Customer behaviour; Digital advertising; Millennials